The Idaho Virtualization Laboratory 3D Pipeline - Nicholas A. Holmer; Nicholas Clement; Kaitlyn Dehart; Herbert Maschner; Jesse Pruitt; Robert Schlader; Myriam van Walsum (Virtual Archaeology Review, 2014)
Three dimensional (3D) virtualization and visualization is an important component of industry, art, museum curation and cultural heritage, yet the step by step process of 3D virtualization has been little discussed. Here we review the Idaho Virtualization Laboratory’s (IVL) process of virtualizing a cultural heritage item (artifact) from start to finish. Each step is thoroughly explained and illustrated including how the object and its metadata are digitally preserved and ultimately distributed to the world.